Pengaruh Literasi Keuangan dan Perilaku Keuangan Terhadap Keputusan Investasi Online - Kasturi, Lukman Firdaus Mahiryahya; Syahputri, Yuni; Marbun, Patar; Khairunnisak, Khairunnisak (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This research aims to analyze and measure the influence of financial literacy and financial behavior on investment decisions. This type of research is associative research. Types and data sources used are primary data that is collected and processed by the researcher himself from the object. The amount of sample in this research is 38 employee of contact center PLN site Medan who were taken by non-probability total sampling. The analytical method used is descriptive analysis method and multiple linear regression analysis method which is processed with SPSS software. The results of this research shows that financial literacy has no significant effect on investment decisions, while financial behavior has a significant effect on investment decisions, and simultaneously shows that financial literacy and financial behavior have a significant effect on investment decisions.